Estudo dos efeitos renais do veneno da serpente Crotalus durissus collilineatus - Amora, Daniela Nascimento (2005)
Crotalus durissus collilineatus is a snake usually found in semideciduous forest, the Cerrado region and its bites constitutes an important health problem. The most serious systemic change and primary cause of death is acute renal failure although the mecanisms of the damaging effects are not totally understood. We investigated the biological effects promoted by Crotalus durissus collilineatus crude venom and its fractions crotoxin and phopholipase A2. The toxic effects of C d collilineatus crude venom were evaluated by the histopathological analysis of organs such as heart, kidney, brain, lung and liver. Wistar rats were inoculated intraperitoneally with C d collilineatus crude venom. The liver showed steatosis and microvacuolation.The other organs showed normal morphological aspects. Renal effects were evaluated by the isolated perfused rat kidney method.The crude venom used at the lowest dose (10µg) increased perfusion pressure (PP), urinary flow (UF), and glomerular filtration rate (GFR), with maximal effect at 120min (PP: control(120) 110.3+/-3.69; venom(120) 126.8+/-10.2; UF: control(120) 0.19+/-0.03; venom(120) 0.23+/-0.06; GFR: control(120) 0.79+/-0.07; venom(120) 1.17+/-0.4). There was no effect on the percent of sodium tubular transport (%TNa+), the percent of potassium tubular transport (%TK+) and the percent of chloride tubular transport (%TCl-) The highest dose of the crude venom (30µg) caused a significantly decrease in PP (control(120) 110.3±3.69; venom(120) 96.7±8.1), RVR (control(120) 6.42±0.78; venom(120)4.8±0.56), UF (control(120) 0.19±0.03; venom(120) 0.12±0.01) and GFR (control(120) 0.79±0.07; venom(120)0.53±0.09). There was not effect on the percent of electrolytes tubular transport (%TNa+, %TK+ and %TCl-). Crotoxin (10mcg) produced a decrease in GFR (control(120) 0.79±0.07; crotoxin(120) 0.31±0.10), while PP, RVR and UF remained stable. Crotoxin also reduced %TK+ (control(120) 69.94±6.49; crotoxin(120) 33.28±4.78) and %TCl- (control(120) 79.53±2.67; crotoxin (120) 64.62±6.93) with maximal effect at 120min. Kidney perfused with phospholipase A2 (PLA2) showed a decrease in GFR (control(120) 0.79±0.07; PLA2 (120) 0.52±0.07) at 120min, whereas PP, RVR, UF and %TNa+ remained stable. PLA2 also reduced %TK+ (control(120) 69.94±6.49; PLA2 (120) 56.26±6.81) and %TCl- (control(60) 82.25±2.72; PLA2 (60) 75.04±4.26) at 60min. These results altogether indicate that Crotalus durissus collilineatus venom caused significative alterations in the renal parameters as well as hepatic damage.